(untitled) (Research, Society and Development, 2020)
The study aimed to know the experiences of adolescents related to hospitalization due to conditions sensitive to Primary Health Care. This is a study with a qualitative approach, conducted in a public reference hospital in Santa Maria. The collection took place through a semi-structured interview that took place in the second semester of 2019. Qualitative data were subjected to Thematic Content Analysis. It is noteworthy that all research was governed by Resolution 466/2012, respecting the ethical aspects of research conducted with humans. For adolescents experiencing hospitalization, negative emotional reactions associated with the rupture and separation of family and peers emerged. Such experiences were also related to the health condition and the technical procedures to which they were submitted during the treatment. For some participants, hospitalization was permeated by ambiguous feelings, as they sometimes understood the importance of treatment to improve their health condition, and sometimes did not accept to have their routine interrupted. The research is expected to improve adolescent health care by identifying the causes of hospitalization for conditions sensitive to primary care, reducing such rates.